From better schools to better nourishment: Evidence from a school-building program in India - Somdeep Chatterjee (IZA Journal of Labor Policy, 2020)
This is a short paper analyzing the potential effects of a targeted school-building program on health indicators. The Kasturba Gandhi Balika Vidyalaya (KGBV) program in India intended to build residential schools for girls from historically disadvantaged sections of the society, providing a unique multifaceted policy setting with tenets of gender equality, affirmative action, and infrastructure reform in education. Exploiting the potentially exogenous cross-sectional variations generated by the institutional features of implementation of this intervention, I run triple-difference regressions to find that the program led to increases in body mass index (BMI) among the underweight. There seems to be a positive correlation between KGBV exposure and probability of being in the "healthy" band of BMI indicators.
Keywords: I25; I28; I12; I15; 330; health; education for girls; BMI; affirmative action